4D flow MRI of type B dissection with later retrograde progression to type A dissection in Marfan: a case report. Issue 8 (27th August 2021) - van Hout, Max J P; Juffermans, Joe F; Scholte, Arthur J; Lamb, Hildo J
Abstract: Background : Due to the malfunction of connective tissue, Marfan patients are at increased risk of aortic dissection. Uncomplicated acute type B dissection is usually managed with medical therapy. Retrograde progression or new type A dissection is a relatively rare but often fatal complication that occur most frequently in the first 6 months after acute type B dissection. Case summary : We present a 31-year-old male with Marfan syndrome and a recent uncomplicated type B dissection from the left subclavian to the right common iliac artery who underwent 4D flow magnetic resonance imaging (MRI). The dissection had a large proximal intimal tear just distal to the left subclavian artery (15 mm) and large false lumen (35 mm). Aortic blood flow just distal to the left subclavian artery (3.6 L/min) was split disproportionately into the true (0.8 L/min, 22%) and false lumen (2.8 L/min, 78%). 4D flow streamlines revealed vortical flow in the proximal false lumen. Increased wall shear stress was observed at the sinotubular junction (STJ), inner wall of the ascending aorta and around the subclavian artery. Two weeks after MRI, the patient presented with jaw pain. Computed tomography showed a type A dissection with an entry tear at the STJ for which an acute valve-sparing root, ascending and arch replacement was performed. Discussion : Better risk assessment of life-threatening complications in uncomplicated type B dissections could improve treatment strategies in these patients. Our case demonstrates that besides clinical and morphological parameters, flow derived parameters could aid in improved risk assessment for retrograde progression from uncomplicated type B dissection to acute type A dissection.